Is there a Credit Channel in Austria? The Impact of Monetary Policy on Firms' Investment Decisions - Katrin Wesche (Oesterreichische Nationalbank (OeNB), 2000)
Though most economists agree that monetary policy has significant effects on the real sector in the short run, interest-rate elasticities of macroeconomic aggregates in general are found to be low. Recently, the credit channel has been discussed as an additional channel through which monetary impulses can exert influence on the real economy. Though the credit channel is difficult to uncover with aggregate data, its distributional implications can be tested with micro data. We investigate balance sheet and income statement data for Austrian firms. Descriptive statistics do not re-ject the notion that monetary policy could have an effect through the so-called bal-ance sheet channel. Panel estimation results show that firms, which are expected to be affected more by asymmetric information and moral hazard problems, are more responsive to internal funds in their investment decisions. Moreover, financial con-straints become more severe in times of restrictive monetary policy.
Keywords: D92; E22; C23; G31; G32; 330; Credit channel; balance sheet channel; investment; panel data